Reconstruction of Collusion and Nepotism in Corruption Policy - Ali Mukartono; Ahmad Dwi Nuryanto; Muhammad Arbani; Mohammed AlHadi Ibrahim Bosha Ahmed (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2025)
The ineffectiveness of the criminal system in addressing collusion and nepotism in Indonesia stem form from normative inequality, multiple interpretations of the law, and a repressive approach that does not address the complexity of power crimes. This research aims to reconstruct the national legal system to combat the lack of norms and weak regulations related to collusion and nepotism as an operational criminal offense. It employs a normative approach with a statute analysis and a comparative study of the United States legal system to enhance normative recommendations. This research shows, first, that there are fundamental differences in legal policies regarding the criminalisation of collusion and nepotism. The United States addresses these issues implicitly through various criminal statutes, while Indonesia integrates them into its anti-corruption regime as a historical response to the abuse of power. Second, normative imbalances in Indonesia, such as the non-operational formulation of the crime of collusion and limited sanctions against nepotism, have led to weak enforcement and created loopholes for the abuse of authority. Therefore, third, it is imperative to reconstruct the law to encompass the aspects of substance, structure, and legal culture, thereby strengthening the effectiveness of criminalisation and addressing collusion and nepotism.